Response of Eight O’clock Flowers (Turnera subulata) to the Short Length of Illumination (Photoperiodism) - Sabrina, Mutia Zakiyyatus; Azzahra, Alya Febrina; Reviana, Hanafi; Indriasari, Tyas; Lestari, Pramesti Ayu; Indriawati, Yastin (Jurnal Biologi Tropis, 2025)
Response of Eight O’clock Flowers (Turnera subulata) to the Short Length of Illumination (Photoperiodism).